2019
DOI: 10.35508/tjph.v1i3.2138
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Sosial Ekonomi Dengan Ketahanan Pangan Rumah Tangga Pedagang Sayur Eceran di Pasar Oeba

Abstract: The success of the development is influenced by several aspects, one of them is food security. Food security can be a reflection of the quality of a nation. A nation with low food security can influence its physical and human development. GFSI states that Indonesia occupies 69 positions in World Food security. Food security can not only be seen in terms of global area but also in terms of households. Greengrocer is the person who works in the informal sector and generally has low income. This research aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Semakin besar pendapatan, semakin besar pula daya beli, sehingga semakin besar tingkat kesejahteraan rumah tangga. Kesejahteraan rumah tangga yang tidak terlepas dari pendapatan membuktikan bahwa ekonomi keluarga menjadi salah satu faktor penentu kesejahteraan keluarga dan juga masalah gizi keluarga (Sitanaya, Aspatria, dan Boeky 2019).…”
Section: Monitoring Dan Evaluasiunclassified
“…Semakin besar pendapatan, semakin besar pula daya beli, sehingga semakin besar tingkat kesejahteraan rumah tangga. Kesejahteraan rumah tangga yang tidak terlepas dari pendapatan membuktikan bahwa ekonomi keluarga menjadi salah satu faktor penentu kesejahteraan keluarga dan juga masalah gizi keluarga (Sitanaya, Aspatria, dan Boeky 2019).…”
Section: Monitoring Dan Evaluasiunclassified
“…Copyright Households with low income tend to focus on allocating income to food needs compared to non-food needs 22 , meeting non-food needs after their food needs are met 23 , and having a low level of food diversity24 so that it can be stated that the level of income is closely related to food and non-food expenditure 24 . Regarding food expenditure, the two regions' expenditure on side dishes and snacks is the most significant.…”
Section: Household Characteristicsmentioning
confidence: 99%
“…Kurniawan et al (2022) find that Low productivity can affect the income of cassava farmers. In a study conducted by Sitanaya et al (2019), it was found that the level of household income has a significant impact on food security status. Households with low income find it challenging to fulfill food needs in the family.…”
Section: Introductionmentioning
confidence: 99%